Composition

JP2025030641APending Publication Date: 2025-03-07ETEC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023136124
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-24
Publication Date
2025-03-07

AI Technical Summary

Benefits of technology

【0011】 本発明に係る組成物によれば、貯蔵安定性に優れるとともに、他の成分との混合安定性にも優れており、組成物に含まれる重合体粒子(A)がバインダーとしての特性を発現することで良好な塗膜を形成することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025030641000001
    Figure 2025030641000001
  • Figure 2025030641000002
    Figure 2025030641000002
  • Figure 2025030641000003
    Figure 2025030641000003
Patent Text Reader

Abstract

To provide a composition containing polymer particles, exhibiting superior storage stability and superior blending stability with other ingredients.SOLUTION: A composition according to the present invention comprises polymer particles (A), a polyvalent anion (B), and a liquid medium (C), wherein the polymer particles (A) have repeating units (Ma) derived from methyl (meth)acrylate and repeating units (Mb) represented by the following general formula (1), and the concentration of the polyvalent anion (B) in the composition is 300 ppm to 2,000 ppm. (In formula (1), R1 represents a hydrogen atom or a methyl group, and R2 represents a C4-10 alkyl group).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composition containing polymer particles. [Background technology]

[0002] Compositions containing polymer particles such as latex are widely used as binders in the fields of paper coating, carpet backsizing, wood products such as plywood and veneer, battery electrodes, tire cords, and the like (see, for example, Patent Documents 1 and 2). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2022-124473 A [Patent Document 2] International Publication No. 2021 / 006211 Summary of the Invention [Problem to be solved by the invention]

[0004] However, such compositions containing polymer particles may freeze when stored in an environment below freezing point, etc., and thus there is still a problem with storage stability. In addition, in the above-mentioned various applications, when the composition containing polymer particles is mixed with other components, there is a problem that the polymer particles aggregate due to the shock during mixing, and sedimentation is likely to occur.

[0005] Some aspects of the present invention provide a composition containing polymer particles that has excellent storage stability and also excellent mixing stability with other components. [Means for solving the problem]

[0006] The present invention has been made to solve at least a part of the above-mentioned problems, and can be realized in any of the following aspects.

[0007] One aspect of the composition according to the present invention is A composition comprising polymer particles (A), a polyvalent anion (B), and a liquid medium (C), The polymer particles (A) have a repeating unit (Ma) derived from methyl (meth)acrylate and a repeating unit (Mb) represented by the following general formula (1), The concentration of the polyvalent anion (B) in the composition is 300 ppm to 2,000 ppm. [ka] (In formula (1), R 1 represents a hydrogen atom or a methyl group, and R 2 represents an alkyl group having 4 to 10 carbon atoms.

[0008] In one embodiment of the composition, The polyvalent anion (B) is SO4 2- may be also possible.

[0009] In any of the above-described embodiments of the composition, The polymer particles (A) may have a number average particle size of 30 nm to 600 nm.

[0010] In any of the above-described embodiments of the composition, The THF insoluble content of the polymer particles (A) may be 60% by mass or more based on 100% by mass of the polymer particles (A). Effect of the Invention

[0011] The composition according to the present invention has excellent storage stability and also excellent mixing stability with other components, and the polymer particles (A) contained in the composition exhibit binder properties, making it possible to form a good coating film. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Preferred embodiments of the present invention will be described in detail below. Note that the present invention is not limited to the following embodiments, and includes various modified examples that are implemented within the scope of the present invention.

[0013] In this specification, "(meth)acrylic" refers to "acrylic" or "methacrylic". Furthermore, "(meth)acrylate" refers to "acrylate" or "methacrylate".

[0014] In this specification, a numerical range described using "X to Y" means that the numerical range includes the numerical value X as the lower limit and the numerical value Y as the upper limit.

[0015] 1. Composition A composition according to one embodiment of the present invention comprises polymer particles (A), a polyvalent anion (B), and a liquid medium (C), wherein the polymer particles (A) have a repeating unit (Ma) derived from methyl (meth)acrylate and a repeating unit (Mb) represented by the following general formula (1), and the concentration of the polyvalent anion (B) in the composition is 300 ppm to 2,000 ppm. [ka] (In formula (1), R 1 represents a hydrogen atom or a methyl group, and R 2 represents an alkyl group having 4 to 10 carbon atoms. Components that may be contained in the composition according to this embodiment will be described in detail below.

[0016] 1.1. Polymer particles (A) The composition according to the present embodiment contains polymer particles (A). The composition according to the present embodiment is preferably in the form of a latex in which the polymer particles (A) are dispersed in a liquid medium (C).

[0017] The repeating units constituting the polymer particles (A), the physical properties of the polymer particles (A), and the synthesis method will be described below in that order.

[0018] 1.1.1. Repeating units constituting polymer particles (A) The polymer particles (A) have a repeating unit (Ma) derived from methyl (meth)acrylate (hereinafter also simply referred to as "repeating unit (Ma)") and a repeating unit (Mb) (hereinafter also simply referred to as "repeating unit (Mb)") represented by the following general formula (1). [ka] (In formula (1), R 1 represents a hydrogen atom or a methyl group, and R 2 represents an alkyl group having 4 to 10 carbon atoms.

[0019] The content of the repeating unit (Ma) is preferably 20 to 95% by mass when the total of the repeating units contained in the polymer particles (A) is taken as 100% by mass. The lower limit of the content of the repeating unit (Ma) is more preferably 30% by mass, and particularly preferably 35% by mass. The upper limit of the content of the repeating unit (Ma) is more preferably 90% by mass, and particularly preferably 85% by mass. By containing the repeating unit (Ma) within the above range, the polymer particles (A) exhibit good storage stability while exhibiting the properties (binding strength) of a binder.

[0020] Specific examples of monomers that provide the repeating unit (Mb) include (meth)acrylic acid alkyl (C4-C10) esters such as n-butyl (meth)acrylate, isobutyl (meth)acrylate, n-amyl (meth)acrylate, isoamyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, nonyl (meth)acrylate, and decyl (meth)acrylate, and may be one or more selected from these. Of these (meth)acrylic acid alkyl (C4-C10) esters, one or more selected from n-butyl (meth)acrylate and 2-ethylhexyl (meth)acrylate are preferred.

[0021] The content of the repeating unit (Mb) is preferably 1 to 75% by mass when the total of the repeating units contained in the polymer particles (A) is taken as 100% by mass. The lower limit of the content of the repeating unit (Mb) is more preferably 3% by mass, and particularly preferably 5% by mass. The upper limit of the content of the repeating unit (Mb) is more preferably 70% by mass, and particularly preferably 60% by mass. By containing the repeating unit (Mb) within the above range, the polymer particles (A) exhibit good storage stability while exhibiting the properties (binding strength) of a binder.

[0022] In addition to the repeating units (Ma) and (Mb), the polymer particles (A) may have repeating units derived from other monomers copolymerizable therewith. Examples of such repeating units include repeating units derived from α,β-unsaturated nitrile compounds, repeating units derived from aromatic vinyl compounds, repeating units derived from unsaturated carboxylic acids, and repeating units derived from unsaturated carboxylate esters (repeating units (Ma) and (Mb)). Repeating units derived from α,β-unsaturated amides are exemplified.

[0023] Specific examples of the α,β-unsaturated nitrile compound include acrylonitrile, methacrylonitrile, α-chloroacrylonitrile, α-ethylacrylonitrile, vinylidene cyanide, etc., and may be one or more selected from these. Among these, it is preferable to use one or more selected from acrylonitrile and methacrylonitrile, and more preferable to use acrylonitrile.

[0024] The content of the repeating units derived from the α,β-unsaturated nitrile compound is preferably 35% by mass or less, and more preferably 3 to 15% by mass, when the total amount of the repeating units contained in the polymer particles (A) is taken as 100% by mass.

[0025] Specific examples of the aromatic vinyl compound include styrene, α-methylstyrene, p-methylstyrene, vinyltoluene, chlorostyrene, 1-ethyl-2-vinylbenzene, divinylbenzene, sodium p-styrenesulfonate, etc., and the aromatic vinyl compound may be one or more selected from these. Of the above, styrene is particularly preferred as the aromatic vinyl compound.

[0026] The content of the repeating units derived from the aromatic vinyl compound is preferably 5 to 45 mass%, and more preferably 10 to 30 mass%, when the total of the repeating units contained in the polymer particles (A) is taken as 100 mass%.

[0027] Specific examples of the unsaturated carboxylic acid include mono- or dicarboxylic acids such as acrylic acid, methacrylic acid, crotonic acid, maleic acid, fumaric acid, itaconic acid, etc., and may be one or more selected from these. In particular, it is preferable to use one or more selected from acrylic acid, methacrylic acid, and itaconic acid.

[0028] The content of the repeating units derived from the unsaturated carboxylic acid is preferably 0.1 to 20 mass%, and more preferably 0.5 to 15 mass%, when the total of the repeating units contained in the polymer particles (A) is taken as 100 mass%.

[0029] The unsaturated carboxylic acid ester is preferably a (meth)acrylic acid ester other than methyl (meth)acrylate and alkyl (C4-C10) (meth)acrylate ester. Specific examples of the (meth)acrylic acid ester include ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, benzyl (meth)acrylate, hydroxymethyl (meth)acrylate, hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, glycidyl (meth)acrylate, ethylene glycol (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, allyl (meth)acrylate, and ethylene di(meth)acrylate, and may be one or more selected from these.

[0030] The content of the repeating units derived from the unsaturated carboxylic acid ester (excluding the repeating units (Ma) and (Mb)) is preferably 0.1 to 10 mass%, and more preferably 0.5 to 5 mass%, when the total of the repeating units contained in the polymer particles (A) is taken as 100 mass%.

[0031] Specific examples of the α,β-unsaturated amide compound include (meth)acrylamide, N,N-dimethyl(meth)acrylamide, and N,N-diethyl(meth)acrylamide, and the like can be one or more selected from these.

[0032] The content of the repeating units derived from the α,β-unsaturated amide compound is preferably 0.1 to 20 mass%, and more preferably 0.5 to 15 mass%, when the total of the repeating units contained in the polymer particles (A) is taken as 100 mass%.

[0033] 1.1.2. Physical properties of polymer particles (A) 1.1.2.1. Tetrahydrofuran (THF) insolubles The THF insoluble content of the polymer particles (A) is preferably 60% by mass or more, more preferably 90% by mass or more, and particularly preferably 95% by mass or more, based on 100% by mass of the polymer particles (A). The THF insoluble content is an index of the solvent resistance and water resistance of the resulting coating film. Therefore, if the THF insoluble content is within the above range, it is considered that the water resistance of the coating film produced using the composition according to this embodiment is good. The method for measuring the THF insoluble content follows the method described in the Examples below.

[0034] 1.1.2.2.Number average particle size The number average particle diameter of the polymer particles (A) is preferably in the range of 30 nm to 600 nm, more preferably in the range of 40 nm to 200 nm. When the number average particle diameter of the polymer particles (A) is within the above range, the surface of the resulting coating film becomes smooth, and a coating film having excellent scratch resistance can be formed.

[0035] The number average particle size of the polymer particles (A) is the particle size (D50) value at which the cumulative frequency of the particle number when the particles are accumulated from the smallest particle by measuring the particle size distribution using a particle size distribution measuring device based on the light scattering method is 50%. Examples of such particle size distribution measuring devices include Coulter LS230, LS100, LS13 320 (all manufactured by Beckman Coulter. Inc.) and FPAR-1000 (manufactured by Otsuka Electronics Co., Ltd.). These particle size distribution measuring devices can evaluate not only the primary particles of the polymer particles, but also the secondary particles formed by the aggregation of the primary particles. Therefore, the particle size distribution measured by these particle size distribution measuring devices can be used as an index of the dispersion state of the polymer particles.

[0036] Transition Temperature The transition temperature of the polymer particles (A) is preferably in the temperature range of -20°C to 150°C, and more preferably -10°C to 135°C, when measured by differential scanning calorimetry (DSC) in accordance with JIS K7121:2012.

[0037] 1.1.3. Method for synthesizing polymer particles (A) The method for synthesizing the polymer particles (A) is not particularly limited, but the polymer particles (A) can be easily prepared, for example, by the emulsion polymerization process described below.

[0038] Examples of monomer components used in the emulsion polymerization step include methyl (meth)acrylate and (meth)acrylic acid alkyl (C4-C10) esters, as well as α,β-unsaturated nitrile compounds, aromatic vinyl compounds, unsaturated carboxylic acids, unsaturated carboxylic acid esters other than methyl (meth)acrylate and (meth)acrylic acid alkyl (C4-C10) esters, and α,β-unsaturated amide compounds.

[0039] In 100% by mass of the total monomer components, the content of methyl (meth)acrylate is preferably from 20 to 95% by mass, more preferably from 30 to 90% by mass, and more preferably from 35 to 85% by mass. % is particularly preferred.

[0040] In 100% by mass of all monomer components, the content of the (meth)acrylic acid alkyl (C4-C10) ester is preferably 1 to 75% by mass, more preferably 3 to 70% by mass, and particularly preferably 5 to 65% by mass.

[0041] The emulsion polymerization step is carried out in an aqueous medium in the presence of an emulsifier, a polymerization initiator, and a chain transfer agent. Each material used in the emulsion polymerization step will be described below.

[0042] Specific examples of the emulsifier include anionic surfactants such as sulfate salts of higher alcohols, aliphatic sulfates, alkylbenzenesulfonates, alkyldiphenyletherdisulfonates, aliphatic sulfonates, aliphatic carboxylates, aliphatic phosphate salts, aliphatic phosphate salts, dehydroabietic acid salts, naphthalenesulfonic acid-formaldehyde condensates, sulfate salts or phosphate salts having a (poly)alkoxy structure, and polymerizable ether sulfate-type ammonium salts; nonionic surfactants such as alkyl esters of polyethylene glycol, alkylphenyl ethers of polyethylene glycol, and alkyl ethers of polyethylene glycol; and fluorine-based surfactants such as perfluorobutylsulfonates, perfluoroalkyl group-containing phosphate esters, perfluoroalkyl group-containing carboxylates, and perfluoroalkylethylene oxide adducts. One or more selected from these can be used.

[0043] Specific examples of the polymerization initiator include water-soluble polymerization initiators such as lithium persulfate, potassium persulfate, sodium persulfate, ammonium persulfate, and 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine] tetrahydrate; and oil-soluble polymerization initiators such as cumene hydroperoxide, benzoyl peroxide, tert-butyl hydroperoxide, acetyl peroxide, diisopropylbenzene hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, azobisisobutyronitrile, and 1,1'-azobis(cyclohexanecarbonitrile). Of these, it is preferable to use potassium persulfate, sodium persulfate, ammonium persulfate, cumene hydroperoxide, or tert-butyl hydroperoxide. The proportion of the polymerization initiator used is not particularly limited, but is appropriately set in consideration of the monomer composition, the pH of the polymerization reaction system, and the combination of other additives.

[0044] Specific examples of chain transfer agents include alkyl mercaptans such as n-hexyl mercaptan, n-octyl mercaptan, tert-octyl mercaptan, n-dodecyl mercaptan, tert-dodecyl mercaptan, and n-stearyl mercaptan; xanthogen compounds such as dimethyl xanthogen disulfide and diisopropyl xanthogen disulfide; thiuram compounds such as terpinolene, tetramethylthiuram disulfide, tetraethylthiuram disulfide, and tetramethylthiuram monosulfide; 2,6-di-tert-butyl-4-methylphenol, styrenated phenol, and the like. allyl compounds such as allyl alcohol; halogenated hydrocarbon compounds such as dichloromethane, dibromomethane, and carbon tetrabromide; vinyl ether compounds such as α-benzyloxystyrene, α-benzyloxyacrylonitrile, and α-benzyloxyacrylamide; as well as triphenylethane, pentaphenylethane, acrolein, methacrolein, thioglycolic acid, 2-ethylhexyl thioglycolate, thiomalic acid, 2-ethylhexyl thioglycolate, and α-methylstyrene dimer, and one or more selected from these can be used.

[0045] The emulsion polymerization step is preferably carried out under conditions of a polymerization temperature of 40 to 80° C. and a polymerization time of 2 to 4 hours.

[0046] After the emulsion polymerization is completed, it is preferable to neutralize the dispersion to a pH of about 5 to 10 by adding a neutralizing agent. The neutralizing agent to be used is not particularly limited, but examples thereof include metal hydroxides such as sodium hydroxide and potassium hydroxide, ammonia, and amine compounds. The pH of the dispersion is set in the range of 5 to 10 to improve the blending stability of the dispersion, preferably 6 to 9, and more preferably 7 to 8.5. If the total solid content concentration in the emulsion polymerization step is 50% by mass or less, the reaction can proceed with good dispersion stability, but is preferably 45% by mass or less, and more preferably 40% by mass or less. In addition, by concentrating after the neutralization treatment, the particle stability can be further improved while achieving high solid fractionation.

[0047] 1.2. Multivalent anions (B) The composition according to the present embodiment contains a polyvalent anion (B). The concentration of the polyvalent anion (B) in the composition according to the present embodiment is 300 ppm to 2,000 ppm, preferably 400 ppm to 1,000 ppm, and more preferably 500 ppm to 800 ppm. When the concentration of the polyvalent anion (B) in the composition is within the above range, the dispersion stability of the polymer particles (A) is improved, so that the storage stability of the composition is improved and aggregation of the polymer particles (A) due to shock when mixed with other components such as an organic solvent can be suppressed.

[0048] The polyvalent anion (B) is not particularly limited as long as it is a polyvalent anion, and may be a carbonate ion (CO 2- ), sulfate ion (SO4 2- ), phosphate ion (PO4 3- ), citrate ion, ascorbate ion, isoascorbate ion, oxalate ion, etc. Among these, sulfate ion (SO4 2- ) is preferable. Sulfate ion (SO4 2- By containing a predetermined amount of (A), the dispersion stability of the polymer particles (A) can be effectively improved, and therefore the storage stability of the composition is dramatically improved.

[0049] To generate the polyvalent anion (B) in the composition according to the present embodiment, a means for dissolving a compound containing the polyvalent anion (B) in the composition can be used. Examples of compounds containing such a polyvalent anion (B) include sulfuric acid, phosphoric acid, iron sulfate (ferrous sulfate, ferric sulfate), aluminum sulfate, aluminum potassium sulfate, magnesium sulfate, magnesium nitrate, magnesium potassium sulfate, zinc sulfate, etc. Among these, sulfuric acid is preferred.

[0050] 1.3. Liquid medium (C) The composition according to the present embodiment contains a liquid medium (C). The liquid medium (C) is preferably an aqueous medium containing water. The aqueous medium can contain a non-aqueous medium other than water. Examples of the non-aqueous medium include amide compounds, hydrocarbons, alcohols, ketones, esters, amine compounds, lactones, sulfoxides, and sulfone compounds, and one or more selected from these can be used. When the liquid medium (C) contains water and a non-aqueous medium, it is preferable that 90% by mass or more of the total amount of the liquid medium (C) is water, and more preferably 98% by mass or more of water. By using an aqueous medium as the liquid medium (C), the composition according to the present embodiment has a low degree of adverse effect on the environment and is safer for the handling workers.

[0051] The content of the non-aqueous medium in the aqueous medium is preferably 10% by mass or less, more preferably 5% by mass or less, and particularly preferably substantially free of the aqueous medium, based on 100% by mass of the aqueous medium. Here, "substantially free of the non-aqueous medium" means that the non-aqueous medium is not intentionally added as a liquid medium, and may include a non-aqueous medium that is inevitably mixed in when the composition is prepared.

[0052] 1.4. Other Additives The composition according to the present embodiment may contain additives other than the above-mentioned components as necessary. Examples of such additives include a thickener, a filler, a preservative, and a pH adjuster.

[0053] <Thickener> Examples of thickeners include cellulose compounds such as carboxymethylcellulose, methylcellulose, and hydroxypropylcellulose; ammonium salts or alkali metal salts of the above cellulose compounds; polycarboxylic acids such as poly(meth)acrylic acid and modified poly(meth)acrylic acid; alkali metal salts of the above polycarboxylic acids; polyvinyl alcohol (co)polymers such as polyvinyl alcohol, modified polyvinyl alcohol, and ethylene-vinyl alcohol copolymers; water-soluble polymers such as saponified copolymers of unsaturated carboxylic acids such as (meth)acrylic acid, maleic acid, and fumaric acid with vinyl esters. Particularly preferred thickeners among these include alkali metal salts of carboxymethylcellulose and alkali metal salts of poly(meth)acrylic acid.

[0054] Commercially available products of these thickeners include, for example, alkali metal salts of carboxymethylcellulose such as CMC1120, CMC1150, CMC2200, CMC2280, and CMC2450 (all manufactured by Daicel Corporation).

[0055] When the composition according to the present embodiment contains a thickener, the amount of the thickener used is preferably 5% by mass or less, and more preferably 0.1 to 3% by mass, based on the total solid content of the composition.

[0056] <Filler> The composition according to this embodiment may improve the hardness of the coating film when formed into a coating film by containing a filler. Examples of the filler include organic fillers and inorganic fillers. Specific examples of the organic filler include polyamide fine particles such as nylon 6, nylon 12, and nylon 66; fluorine-based fine particles such as tetrafluoroethylene and vinylidene fluoride; olefin-based fine particles such as polyethylene and polypropylene; polyester-based fine particles such as polyethylene terephthalate and polyethylene naphthalate; crosslinked particles such as divinylbenzene and polyfunctional acrylates; and rubber fine particles such as natural rubber, isoprene rubber, and acrylic rubber. Specific examples of the inorganic filler include fused spherical silica, fumed silica, sol-gel silica, etc., aluminum oxide, aluminum hydroxide, calcium carbonate, calcium hydroxide, barium sulfate, barium carbonate, magnesium oxide, magnesium hydroxide, and other inorganic fillers derived from minerals such as talc and mica. One or more of these can be used.

[0057] <Preservative> The composition according to this embodiment can suppress the growth of bacteria, mold, etc. and the generation of foreign substances when storing the composition by containing a preservative. Specific examples of the preservative include 1,2-benzisothiazolin-3-one, 2-methyl-4,5-trimethylene-4-isothiazolin-3-one, 2-methyl-4-isothiazolin-3-one, 5-chloro-2-methyl-4-isothiazolin-3-one, N-n-butyl-1,2-benzisothiazolin-3-one, 2-n-octyl-4-isothiazolin-3-one, 4,5-dichloro-2-n-octyl-4-isothiazolin-3-one, etc. One or more of these can be used.

[0058] <pH adjuster> The composition according to this embodiment adjusts the pH to 5 to 9 by adding a pH adjuster By adjusting the pH to 5 to 9, the dispersion stability of the polymer particles (A) may be improved, and the storage stability may be excellent. Examples of the pH adjuster include acidic compounds such as hydrochloric acid, phosphoric acid, sulfuric acid, acetic acid, and formic acid; and basic compounds such as potassium hydroxide, ethylenediamine, monoethanolamine, TMAH (tetramethylammonium hydroxide), TEAH (tetraethylammonium hydroxide), and ammonia.

[0059] In the present invention, pH refers to hydrogen ion exponent, and its value can be measured using a commercially available pH meter (for example, a tabletop pH meter manufactured by Horiba, Ltd.) under conditions of 25° C. and 1 atmospheric pressure.

[0060] 2. Working Example The present invention will be described below with reference to examples, but the present invention is not limited to these examples. In the examples, "parts" and "%" are by weight unless otherwise specified.

[0061] 2.1 Example 1 2.1.1. Synthesis of polymer particles (A) After thoroughly replacing the inside of a 3L separable flask with nitrogen, 50.0 parts by mass of ion-exchanged water and 0.1 parts by mass of ammonium persulfate were charged. The inside temperature was adjusted to 80°C while stirring, and 60.0 parts by mass of ion-exchanged water, 50.0 parts by mass of methyl methacrylate (MMA), 46.0 parts by mass of 2-ethylhexyl acrylate (EHA), 3.0 parts by mass of methacrylic acid (MAA), 1.0 parts by mass of allyl methacrylate (AMA), and 5.0 parts by mass of emulsifier "Kuraray Poval 5-88" (trade name, manufactured by Kuraray Co., Ltd.) were mixed and stirred in a separate container to prepare an emulsion, and the obtained emulsion was continuously dropped into the above reaction container over 3 hours. After the dropwise addition, the mixture was stirred for another 3 hours at 80°C, cooled to 40°C, and 0.1 parts by mass of ammonia water was added to obtain an aqueous dispersion of polymer particles (A).

[0062] 2.1.2. Measurement of THF insolubles About 10 g of the obtained aqueous dispersion was weighed into a Teflon petri dish with a diameter of 8 cm and dried at 120° C. for 1 hour to form a membrane. 1 g of the obtained membrane (polymer) was immersed in 50 mL of tetrahydrofuran (THF) and shaken at 25° C. for 24 hours. Next, the THF phase was filtered through a 300-mesh wire screen to separate the insoluble matter, and the weight (Y(g)) of the residue obtained by evaporating and removing the dissolved THF was measured. From the measured value, the THF insoluble matter of the polymer particles was calculated using the following formula (2), and it was found that the THF insoluble matter was 95%. THF insolubles (%) = ((1-Y) / 1) × 100 (2)

[0063] 2.1.3. Preparation of the Composition To 1,000 g of the aqueous dispersion containing the polymer particles (A) obtained above, an aqueous solution containing 0.5% sulfuric acid was added as necessary, and a composition was prepared so as to have the polyvalent anion content shown in Table 1.

[0064] The particle size distribution of the obtained composition was measured using a particle size distribution measuring device (manufactured by Otsuka Electronics Co., Ltd., model "FPAR-1000") using the dynamic light scattering method as the measurement principle, and the number average particle diameter (D50) was calculated from the particle size distribution, and the number average particle diameter (D50) was 600 nm.

[0065] The content of polyvalent anions in the composition can also be confirmed by analyzing the composition according to the following procedure. That is, the composition prepared as described above was quantified using an ion chromatography analyzer (Dionex ICS-6000, manufactured by Thermo Fisher Scientific Co.), and the content of sulfate ions was confirmed to be 400 ppm. I was able to acknowledge it.

[0066] Evaluation method <Evaluation of viscosity change rate> In various applications, water-soluble organic solvents such as ethylene glycol are often used as a solvent when various additives and optional components are added and blended into the composition. Therefore, if the viscosity increase rate after heating at 60°C when ethylene glycol is added is small, it is considered that other components can be stably blended into the composition. Specifically, when the composition is used for painting or dyeing applications, if the viscosity increase rate after heating at 60°C when ethylene glycol is added is small, the viscosity increase can be suppressed even if other components required for the application are added during use, and there is an advantage that the spray, nozzle, head, etc. of the painting equipment are less likely to become clogged.

[0067] (Evaluation method) 10 g of ethylene glycol was added to 100 g of the composition prepared above and stirred for 5 minutes, after which the viscosity was measured at 25°C using a B-type viscometer. This composition was then heated at 60°C for 24 hours, and the viscosity was measured when it was returned to 25°C, and the rate of viscosity change was calculated using the following formula. The evaluation criteria were as follows. The results are also shown in Table 1. Viscosity change rate (%) = [(viscosity after storage at 60°C for 24 hours) - (viscosity after addition of ethylene glycol)] / (viscosity after addition of ethylene glycol) x 100 (Evaluation Criteria) If the viscosity change rate is less than ±10%, the blending suitability is judged to be good and the grade is "A"; If the viscosity change rate is between ±10% and 100%, it is deemed suitable for blending and can be used in practical applications, and is marked as "B." If the viscosity change rate is more than ±100% or if coagulation occurs, the material is deemed to be unsuitable for blending and cannot be used in practice, and is marked as "C."

[0068] <Freezing temperature evaluation> Generally, such compositions are stored in large quantities in a factory in preparation for use. The compositions stored in large quantities are then consumed as needed. In this case, the temperature of the storage environment of the composition cannot be strictly controlled from the viewpoint of cost, and the composition is often exposed to an environment close to 0°C due to changes in air temperature. For this reason, in the evaluation of the freezing temperature described below, a large change in particle size at 0°C is not acceptable. If the composition does not freeze at -5°C and the change in particle size is small, it can be determined that the composition has high storage stability and is very good. In addition, even if the composition is frozen at -5°C, it is required that the change in particle size is small when the temperature is raised again to room temperature compared to before freezing.

[0069] (Evaluation method) The composition prepared above was filled in a plastic bottle at 1000 g, and then stored in a freezer at -5°C for 24 hours, and the presence or absence of freezing was visually evaluated. The composition was then heated to 25°C, the number average particle size was measured, and the rate of change in particle size was calculated using the following formula. The evaluation criteria are as follows. The results are also shown in Table 1. Particle size change rate (%) = [(number average particle size when the composition is stored at -5°C for 24 hours and then returned to 25°C) - (number average particle size of the composition immediately after preparation)] / (number average particle size of the composition immediately after preparation) x 100 (Evaluation Criteria) If the composition does not freeze and the particle size change rate is less than 10%, it is considered very good and is given an "A" rating. If the composition freezes but the particle size change rate is less than 10%, it is considered good and given a grade of "B". If the composition freezes and the particle size change rate is 10% or more, it is judged as defective and given a grade of "C". It was written as follows.

[0070] 2.2. Examples 2 to 12 and Comparative Examples 1 to 2 In "2.1.1. Synthesis of polymer particles (A)" of the above Example 1, the monomer composition and the types and amounts of the chain transfer agent, emulsifier, polymerization initiator, and additives were changed as shown in Tables 1 and 2 below, but an aqueous dispersion containing polymer particles having the composition shown in Tables 1 and 2 below was prepared in the same manner as in Example 1. Otherwise, a composition was prepared and evaluated in the same manner as in Example 1 above.

[0071] 2.3.Evaluation Results Tables 1 and 2 below show the monomer composition, types and amounts of chain transfer agents, emulsifiers, polymerization initiators, and additives used in the synthesis of polymer particles in each Example and Comparative Example, the properties of the polymer particles, and the evaluation results.

[0072] [Table 1]

[0073] [Table 2]

[0074] The following products or reagents were used for each component in Tables 1 and 2 above. <Methyl (meth)acrylate> MMA: Methyl methacrylate (manufactured by Mitsubishi Chemical Corporation, product name "Acryester M") <(Meth)acrylic acid alkyl (C4-C10) ester> BA: Butyl acrylate (manufactured by Mitsubishi Chemical Corporation, product name "Butyl acrylate") EHA: 2-Ethylhexyl acrylate (manufactured by Nippon Shokubai Co., Ltd., product name "2-Ethylhexyl acrylate") <Other monomers> ST: Styrene (NS Styrene Monomer Co., Ltd., product name "Styrene Monomer") EMA: Ethyl methacrylate (manufactured by Mitsubishi Chemical Corporation, product name "Acryester E") EDMA: Ethylene glycol dimethacrylate (manufactured by Mitsubishi Chemical Corporation, product name "Acryester ED") AMA: Allyl methacrylate (manufactured by Mitsubishi Chemical Corporation, product name "Acryester A") AA: Acrylic acid (manufactured by Toagosei Co., Ltd., product name "acrylic acid") · MAA: Methacrylic acid (manufactured by Mitsubishi Chemical Corporation, product name "MAA") NaSS: Sodium p-styrenesulfonate (manufactured by Tosoh Finechem Corporation, product name "Spinomer Nass") HEMA: 2-hydroxyethyl methacrylate (manufactured by Mitsubishi Chemical Corporation, product name "Acryester HO") <Chain transfer agent> NDM: n-dodecyl mercaptan (manufactured by Kaneda Co., Ltd., product name "N-dodecyl mercaptan") <Emulsifier> Kuraray Poval 5-88: Polyvinyl alcohol (manufactured by Kuraray Co., Ltd., product name "Kuraray Poval 5-88") SDS: Sodium dodecyl sulfate (Kao Corporation, product name "EMAL 2FG") E-118B: Sodium polyoxyethylene alkyl ether sulfate (manufactured by Kao Corporation, product name "Latemul E-118B") SDBS: Sodium dodecylbenzenesulfonate (manufactured by Kao Corporation, product name "Neopelex G-25") JONCRYL 60J: Ammonium salt of modified styrene-acrylic resin (manufactured by BASF Japan Ltd., product name "JONCRYL 60J") SR-1025: (Manufactured by ADEKA Corporation, product name "ADEKA REASOAP SR-1025", ammonium salt of α-sulfo-ω-(1-alkoxy)methyl-2-(2-propenyloxy)ethoxy-poly(oxy-1,2-ethanediyl)) E147: Poly(oxyethylene) dodecyl ether (Kao Corporation, product name "Emulgen 147") <Polymerization initiator> APS: Ammonium persulfate (manufactured by Mitsubishi Gas Chemical Company, Inc., product name "Ammonium persulfate") <Additives> IPA: Isopropanol (Tokuyama Corporation, product name "Tokuso IPA") Ammonia water: (manufactured by Taisei Kako Co., Ltd., product name "Ammonia", pH adjuster)

[0075] According to the evaluation results in Tables 1 and 2, the compositions according to the present invention shown in Examples 1 to 12 had a particle size change rate of less than 10% and generally had high storage stability. Furthermore, the compositions according to the present invention shown in Examples 1 to 12 had a low viscosity change rate even when mixed with ethylene glycol, and the polymer particles did not settle, so that the mixing stability was also excellent.

[0076] In contrast, the composition shown in Comparative Example 1, which contains 40 ppm of polyvalent anion, showed a tendency for the polymer particles to settle and thicken when mixed with ethylene glycol, indicating poor mixing stability. It was found that a content of 4,000 ppm resulted in a 10% change in particle size, resulting in poor storage stability.

[0077] The present invention is not limited to the above-described embodiments, and various modifications are possible. For example, the present invention includes configurations that are substantially the same as those described in the embodiments (for example, configurations with the same functions, methods, and results, or configurations with the same purpose and effect). The present invention also includes configurations in which non-essential parts of the configurations described in the embodiments are replaced. The present invention also includes configurations that achieve the same effects as the configurations described in the embodiments, or configurations that can achieve the same purpose. The present invention also includes configurations in which publicly known technology is added to the configurations described in the embodiments.

Claims

1. A composition comprising polymer particles (A), a polyvalent anion (B), and a liquid medium (C), The polymer particles (A) have a repeating unit (Ma) derived from methyl (meth)acrylate and a repeating unit (Mb) represented by the following general formula (1), A composition, wherein the concentration of the polyvalent anion (B) in the composition is 300 ppm to 2,000 ppm. 【Chemistry 1】 (In formula (1), R 1 represents a hydrogen atom or a methyl group, R 2 represents an alkyl group having 4 to 10 carbon atoms.

2. The polyvalent anion (B) is SO 4 2- 2. The composition of claim 1 ,

3. The composition according to claim 1 or 2, wherein the number average particle diameter of the polymer particles (A) is 30 nm to 600 nm.

4. The composition according to claim 1 or 2, wherein the THF-insoluble content of the polymer particles (A) is 60 mass% or more based on 100 mass% of the polymer particles (A).

Citation Information

Patent Citations

  • White ink and inkjet recording method

    JP2022124473A

  • Ink and ink-jet recording method

    WO2021006211A1